PERANCANGAN POMPA AIR TENAGA SURYA GUNA MEMINDAHKAN AIR BERSIH KE TANGKI PENAMPUNG - Budi Hartono; Purwanto Purwanto (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2015)
Clean water is a basic need of every human being, whether for drinking, cooking, bathing, washing, and others. Then every life can not be separated from the water needs. The availability of water is a reflection of the good life and can improve the quality standard of the local economy. Today to take water from a water source that is easy enough to use the water pump because it is efficient and easy to get a water pump according to the needs of each, but the problem that often arises is the driving source of the water pump is the availability of electricity especially for rural areas untouched state electricity grid. In the Indonesia region passed the equator, the availability of sunlight is abundant and free. This then can be used as a source of electrical energy to drive the water pump proficiency level with a set of solar cell panels. With the design of solar water pumps, 988 Watt peak (Wp) generated power of the solar cell so that it can to meet the needs of clean water daily for 15 m3/day.